Novel Immune Checkpoints in Esophageal Cancer: From Biomarkers to Therapeutic Targets - Zhou, Xueyin; Ren, Ting; Zan, Hongyuan; Hua, Chunyan; Guo, Xufeng (Frontiers in Immunology, 2022)
Esophageal cancer ranks as the sixth most common cause of cancer death worldwide. Due to the limited efficacy of conventional therapeutic strategies, including surgery, chemotherapy, and radiotherapy, treatments are still far from satisfactory in terms of survival, prompting the search for novel treatment methods. Immune checkpoints play crucial roles in immune evasion mediated by tumor cells, and successful clinical outcomes have been achieved via blocking these pathways. However, only a small fraction of patients can benefit from current immune checkpoint inhibitors targeting PD-1/PD-L1 and CTLA-4. Unfortunately, some patients show primary and/or acquired resistance to immune checkpoint inhibitors. Until now, novel immune checkpoint pathways have rarely been studied in esophageal cancer, and there is a great need for biomarkers to predict who will benefit from existing strategies. Herein, we discuss primarily the roles of new immune checkpoints as predictive biomarkers and therapeutic targets for esophageal cancer. In addition, we also summarize the ongoing clinical trials and provide future research directions targeting these pathways.